2011
DOI: 10.1001/jama.2011.678
|View full text |Cite
|
Sign up to set email alerts
|

Management of Women With BRCA Mutations

Abstract: Ms E, a 41-year-old BRCA1 mutation carrier, was diagnosed 4 years ago as having breast cancer and opted for breast-conserving therapy. Prior to receiving chemotherapy, she harvested her eggs through in vitro fertilization and subsequently used preimplantation genetic diagnosis; 3 months ago she delivered a healthy boy. This review examines the prevalence of BRCA mutations in women with breast cancer, as well as current recommendations for surgery and systemic therapy in these women. In particular, the risk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 103 publications
0
18
0
Order By: Relevance
“…However, the high incidence of contralateral breast cancer in CHEK2 1100delC mutation carriers found in the current study (10-year risk 24.1%) and in earlier studies is comparable to the incidence of contralateral breast cancer that we observed in BRCA1 and BRCA2 mutation carriers in an earlier study (10-year risk 25% and 20%, respectively) (Brekelmans et al , 2006) and in line with observations of other groups (10-year risk ranging between 13 and 37%) (Haffty et al , 2002; Metcalfe et al , 2004; Robson et al , 2005; Pierce et al , 2006; Graeser et al , 2009; van der Kolk et al , 2010). Based on this increased contralateral breast cancer rate, affected BRCA1/2 mutation carriers have a more intensive follow-up scheme for contralateral breast cancer detection including MRI or can opt for a risk-reducing contralateral mastectomy, even though it is unknown whether such a risk-reducing contralateral mastectomy can improve survival (Tung, 2011). In our opinion, this follow-up regimen should also be offered to CHEK2 1100delC mutation carriers after breast cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the high incidence of contralateral breast cancer in CHEK2 1100delC mutation carriers found in the current study (10-year risk 24.1%) and in earlier studies is comparable to the incidence of contralateral breast cancer that we observed in BRCA1 and BRCA2 mutation carriers in an earlier study (10-year risk 25% and 20%, respectively) (Brekelmans et al , 2006) and in line with observations of other groups (10-year risk ranging between 13 and 37%) (Haffty et al , 2002; Metcalfe et al , 2004; Robson et al , 2005; Pierce et al , 2006; Graeser et al , 2009; van der Kolk et al , 2010). Based on this increased contralateral breast cancer rate, affected BRCA1/2 mutation carriers have a more intensive follow-up scheme for contralateral breast cancer detection including MRI or can opt for a risk-reducing contralateral mastectomy, even though it is unknown whether such a risk-reducing contralateral mastectomy can improve survival (Tung, 2011). In our opinion, this follow-up regimen should also be offered to CHEK2 1100delC mutation carriers after breast cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…It may not improve overall survival, however, relative to routine mammography and MRI use, particularly for women who have had their ovaries removed [27]. Contralateral prophylactic mastectomy (CPM; surgical removal of the nonaffected breast for women with unilateral breast cancer) has not been shown to improve survival rates, but may decrease the risk of contralateral cancers in certain high-risk women; it is considered a clinically appropriate option for breast cancer patients with known BRCA1/2 mutations, significant family history, or high-risk histology [3238]. …”
Section: Breast Cancer Prevention Pathwaysmentioning
confidence: 99%
“…BPSO is likely more common than BPM among BRCA mutation carriers because ovarian cancer treatment has poorer success rates than breast cancer treatment, because BPSO reduces risk of both ovarian and breast cancer, and because some women find mastectomy more psychologically difficult due to its potential effects on body image and sexuality [85]. CPM rates have risen substantially in recent decades, mostly among women who are BRCA -mutation negative or do not know their genetic status, and who are therefore unlikely to benefit [32, 38, 41, 43, 82, 8689]. More than 5% of these women currently undergo CPM even as rates of contralateral breast cancer and regional breast cancer recurrence are both dropping; this raises concerns about surgery-related health risks, the need for new methods of communication about surgical options, and over-utilization of health services [42, 82, 89].…”
Section: Women’s Prevention Choicesmentioning
confidence: 99%
“…The knowledge on how BRCA1/2 mutation carriers should be counseled and treated has evolved continuously over the last two decades [1, 2]. Some important issues remain to be solved, though.…”
Section: Introductionmentioning
confidence: 99%